Implementasi Sistem Pengambil Keputusan Perekrutan Karyawan Pada Bank Rakyat Indonesia Cikampek - Ismasari Nawangsih (Jurnal Pelita Teknologi, 2020)
To get a work process data sorting solution for job applicants can be implemented quickly, precisely and design an employee recruitment information system that can be used to input job applicant data and sort it according to the criteria needed by the company. The method used in this study uses OOP (Object Oriented Programming) which is object-oriented programming. All data and functions in this paradigm are wrapped in classes or objects. Each object can receive messages, process data, and send messages to other objects. The object-oriented data model is said to provide more flexibility, ease of changing programs, and is widely used in large-scale software techniques. OOP is more easily developed and maintained. The system testing process uses the black box method. Based on the results of alpha testing with sample test cases on the Application System for recruiting new employees using the Black box method, overall on each display the results of this alpha test can be said to be successful or accepted. Because functionally the system can work and produce the expected output. Based on the results of this test it can be concluded that this software is as expected, meets the needs of users and is free of errors so that it is feasible to use. Based on beta testing the employee recruitment system is in accordance with user requirements. This recruitment information system is designed on the basis of a website so that it can be accessed by applicants from anywhere without the need to come to the company. By implementing an employee recruitment information system, HRD performance will be more effective and can save operational costs. Keywords: Information system design, Employee Recruitment, Object Oriented Programming.